Pengaruh Konten Instagram Halodoc Terhadap Pemenuhan Kebutuhan Informasi Kesehatan Gen Z - Azrumi El Ghazali; Sarah Samaria (Institut Nalanda, 2024)
The development of advances in information technology has made it easier for humans to obtain information more effectively, efficiently, and of course more quickly. Social media is one of the latest information platforms that has been widely used in Indonesia, especially by the younger generation or often referred to as Gen Z. According to we are social data in 2018, around 130 million Indonesians who are Gen Z are users of social media. biggest. The use of social media as a provider of information needs can be seen from the content in the related Instagram account. One piece of information that is very important is information regarding the health aspect. One account that utilizes content related to health information is Halodoc. Based on the results of a survey conducted by Daily Research in 2019, Halodoc has become the best digital health service commercial application in Indonesia. This study aims to determine the effect of using Instagram @halodoc content on providing Gen Z health information needs. This type of research uses a quantitative approach by taking a sample of 100 Halodoc followers who belong to the Gen Z category, namely 15-23 years old. From the research results, it can be seen that there are positive results between the two variables. Therefore, it can be concluded that there is an influence of Halodoc Instagram content on providing the information needs of Gen Z